PENGARUH MODEL PEMBELAJARAN SNOWBALL THROWING TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV PADA MATA PELAJARAN BAHASA INDONESIA - Maya, Klaudia; Safrihady, Safrihady; Suwanto, Insan (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to: (1) determine the effect of the Snowball Throwing learning model on students’ reading comprehension skills, and (2) measure the magnitude of its effect on reading comprehension in Indonesian language learning. This quantitative research employed a quasi-experimental method with a nonequivalent control group design. The population consisted of two classes: an experimental group and a control group. Data were collected using a measurement technique with reading comprehension tests administered as pretest and posttest. Before hypothesis testing, normality and homogeneity tests were conducted, showing that the data were normally distributed and homogeneous. Therefore, hypothesis testing was carried out using an independent samples t-test and effect size analysis. The results showed that the Snowball Throwing model had an effect on students’ reading comprehension skills, with the mean score increasing from 52.40 (pretest) to 74.80 (posttest). The independent samples t-test resulted in a significance value of 0.002 (< 0.05), indicating a significant difference between the experimental and control groups. The effect size was 0.901, categorized as large. In conclusion, the Snowball Throwing learning model has a significant and strong effect on improving students’ reading comprehension skills.